The effects of video‐driven discussions integrated into the flipped classroom model on learning achievement, practical performance, and higher‐order thinking skills in dental education. - Fidan, Muhammet; Fidan, Mustafa (Journal of Computer Assisted Learning, 2024)
Background: Flipped classroom (FC) model has become increasingly popular in dental education (DE) with its strengths for students. However, major concerns are lack of interaction, unwillingness to complete the assignments, low engagement during the pre‐class activities because of an unwell‐designed instructional setting of FC. Objectives: The recent study aims to investigate the effects of video‐driven discussions integrated into the flipped classroom (VdDs‐FC) model on dental students' (DSs) learning achievement, practical performance, and higher‐order thinking skills in a restorative dentistry course. Methods: This study adopted a sequential explanatory design from mixed‐methods research. A total of 96 DSs participated in a dentistry faculty of Türkiye. They were randomly divided into two groups: VdDs‐FC group and the conventional flipped classroom (c‐FC) group. Results and conclusions: The results showed that the VdDs‐FC model had significant positive effects on the practical performance of DSs in practical subjects and their problem‐solving and critical thinking skills. However, there was no significant difference between the two groups in learning achievement and creativity. The use of FC in the c‐FC group did not lead to any difference in the students' achievements. Moreover, the qualitative results indicated that the VdDs‐FC model has the potential for enhancing peer learning, practical classroom activities, and higher‐order thinking skills. Implications: This study also includes several instructional implications and suggestions for educators, researchers, and practitioners on use of FC in dentistry. Lay Description: What is already known about this topic: Flipped learning has become a rapidly growing area of dentistry research.Discussion board could be beneficial to increasing dental students' higher order thinking skills, especially problem solving and critical thinking.Video‐driven discussions into flipped classroom provide several opportunities for practical performance in dental education, not for theoretical knowledge. What this paper adds: Video‐driven discussions into flipped classroom model is proposed.We compared two learning environments by including traditional flipped classroom.We found that the integrated model with flipped classroom can have a positive impact on students' achievement.Online discussions usage contributed to higher cognitive, affective, and behavioural learning outcomes.Based on interview data, the proposed model supports peer learning. Implications for practice and/or policy: Dental educators should integrated the digital discussion boards as out‐of‐class activities in the pre‐clinical dental training.From dental educators' perspective, they should be carefully trained in FC design (interaction elements, material design, integration with different methods, etc.).From instructional design perspective, micro videos should have case‐based or problem‐based activities to discuss.From learner perspective, an integration of the flipped classroom with different technologies could have a positive effect on increasing learning.